Uso de las TIC en el aprendizaje de lengua y comunicación, en el octavo año de educación general básica, año 2014 - Tumbaco Diaz, Blanca Lidia (2015)
This research was did with the purpose of obtaining appropriate information about use of Tic’s in the learning processes of the subject of Language and Communication applied in the school of basic education “Consejo Provincial de Cotopaxi” in eighth years. This thesis provides scientific content in the use of TIC, which is based on the use of different technological or computer media for storing, processing, and to publicize all kinds of information. TIC in the education system should be considered as a complement to tools and the existing pedagogical strategies, in other words that application goes beyond the computer labs. Through this research will be provided tools for the process of learning of language and communication, benefiting students and teachers from in the school “Consejo Provincial de Cotopaxi”.